IMPLEMENTASI BANTUAN KEUANGAN KEPADA PARTAI POLITIK - Chitra Imelda*; Liza Nofianti (Jurnal Tengkhiang, 2022)
The importance of law and politics for the financing of political parties, where laws are made according to treatises that perpetuate the hopes and dreams of the people as expressed by their elected officials. In accordance with Government Regulation Number 1 of 2018 concerning the Second Amendment to Government Regulation Number 5 of 2009 concerning Financial Assistance to Political Parties. The aim of this study is to analyze financial assistance to political parties in accordance with government regulations and to determine the implementation of political party accountability for APBN/APBD financial assistance regulated in government regulations. Normative juridical research is conducted by looking at issues from a legal perspective, with source materials including relevant laws and cases, as well as theoretical and philosophical legal frameworks. The results of this study indicate that there are administrative sanctions in the form of cutting APBN/APBD funds for political groups who do not properly account for their income and expenses from APBN/APBD assistance.